The Influence of Organizational Citizenship Behavior and Teamwork on Organizational Commitment with Organizational Culture as an Intervening Variable in Bpjs Employment Branch Offices in Medan Raya - Apri Tantri Hutagaol; Isa Indrawan (International Journal of Society and Law, 2024)
One of the companies that carry out human resource management is BPJS Ketenagakerjaan (Employment Social Security Organizing Agency) is a public program that provides protection for workers to overcome certain socio-economic risks and its implementation uses a social insurance mechanism as a State institution engaged in social insurance BPJS Ketenagakerjaan which was formerly known as PT Jamsostek (Persero) is the implementer of the law The results of this study are as follows: Organizational Culture has a positive and significant effect on Organizational Commitment with a value of 0.431 and a sig of 0.000. Teamwork has a positive and significant effect on Organizational Culture with a value of 0.347 and a sig of 0.001. Teamwork had a positive and significant effect on Organizational Commitment with a value of 0.380 and a sig of 0.001. Organizational Citizenship Behavior had a positive and significant effect on Organizational Culture with a value of 0.573 and a sig of 0.000. Organizational Citizenship Behavior had a psoitative and significant effect on Organizational Commitment with a value of 0.113 and a sig of 0.204. Teamwork has an indirectly positive and significant effect on Organizational Commitment through Organizational Culture with a value of 0.150 and a sig of 0.007. Organizational Citizenship Behavior has an indirect, positive and significant effect on Organizational Commitment through Organizational Culture with a value of 0.247 and a sig of 0.000.